Improving the project competency development process for English language teachers - Usmanova, Komola Khikmatullaevna (The Lingua Spectrum, 2026)
The article discusses the “project method,” which describes a form of work where students are actively involved in organizing their activities. This method unfolds through several stages, beginning with immersion in a topic and defining benchmarks, and progressing to planning the actual work. For general education, mini-projects and micro-research are highlighted as particularly effective. In these formats, the entire inquiry cycle - from asking a question, gathering data, to concluding – can be completed within a few lessons. The article suggests that even young children, specifically those aged 7–10, are capable of planning, assigning roles among themselves, independently finding sources, and critically evaluating information. Modern applications of this method intentionally connect the project to fundamental curriculum concepts, providing an exhibition of proverbs, which presumably links to language arts or cultural studies. So, the arguments presented highlight the project method as a pedagogical approach that can foster comprehensive learning, leverage the capabilities of young students, and align with broader curricular goals - making it a potentially powerful tool for general education systems.